Composição botânica e qualidade do pasto selecionado por ovelhas em caatinga raleada e enriquecida - Alexandre Ribeiro Araújo (2015)
This study was conducted in order to determine the botanical composition and diet quality selected by sheep through fecal micro-histological technique, in thinned and enriched caatinga with Massai grass (Panicum maximum cv Massai.), receiving different amounts of concentrate (0; 200; 350 and 500 g of concentrate per day) at different periods (wet, transition wet-dry and dry). Were also estimated the intake, digestibility, as well as the degradability of forage species eaten by sheep. The experiments were performed in the "Fazenda Crioula do Meio", owned by Embrapa Goats and Sheep, in Sobral, Ceará State, Brazil, from march to november 2013. In Trial 1, sixteen female, pregnant, multiparous, with average body weight of 30,58+2,48 kg Somalis brasileira breed sheep were used to determine the botanical composition and the quality of the selected diet. The monitoring of pasture intake of sheep were conducted in three phenological periods of the caatinga's pasture (wet season, transition wet-dry and dry season). Plant samples were collected for the preparation of the reference slides, with subsequent identification and characterization of epidermal descriptors. The same was done for the feces collected in sheep. Considering the proportion of each species identified in fecal slides which composed the diet, and the chemical composition of forage identified, it was possible to determine the quality of the selected diet. From 76 species observed in the pasture, 33 species was identified in the sheep selected diet, emphasizing the Sabiá (Mimosa caesalpiniaefolia), centrosema (Centrosema sp.), ervanço (Alternanthera brasiliana), massai (Panicum maximum cv Massai) e paco-paco (Wissadula rostrata) as the most selected species by sheep during the study, composing more than 50% of the selected diet. In the Dry Season, undesirable species like marmeleiro (Croton sonderianus) and mofumbo (Combretum leprosum), were also constituent of the diet. Regarding to the nutritional value of selected diet, the sheep selected a diet with more protein than the sampled in the pasture. In the final late gestation, the sheep without supplementation ate a diet above 16% of CP, higher than the selected diet by treatments 350 and 500 g of concentrate per day (P<0.05). Were also observed to the non supplemented sheep, less fiber content intake (P<0.05). In the Trial 2, in the same condition of the first Trial, thirty two Somalis brasileira female sheep were used to determine the intake and digestibility, conducted in three assays (April - third late pregnancy; June - lactation and August - weaning). To predict the intake, the marker LIPE was used. Sheep and lambs were weighted every two weeks to performance evaluation. The concentrate offered to sheep favored to higher intake and digestibility of DM and CP than non supplemented sheep, with inverse relationship to the pasture intake (P<0.05). For the Dry Season, lower intake were observed than for Wet Season and Transition Wet-Dry (P<0.05). Higher intakes and digestibility of the fiber constituents were verified to non supplemented sheep (P<0.05). To performance evaluation, the offered supplementation determined the higher weights observed during lactation and weaning of sheep, and to birth and weaning weights of lambs (P<0.05). In Trial 3, two male sheep were used to determine the degradability of dry matter (DM), crude protein (CP) and neutral detergent fiber (NDF) of five forages selected by sheep in Trial 1: M. caesalpiniaefolia, A. brasiliana, P. maximum cv. Massai, jurema-preta (Mimosa tenuiflora) and C. lepreosum, at zero, 6, 24, 48, 72 and 96 hours of incubation. For each forage, were determined equations for the disappearance of DM, CP and NDF. It was also realized the protein fractions in their degradable and non-degradable in the rumen parts. Was detected a higher disappearance of DM, CP and NDF, as also better proportion of the rumen degradable protein to A. brasiliana, followed by P. maximum cv. Massai and M. caesalpiniaefolia. With the information obtained, it is concluded that the fecal micro histological technique presents as a viable technique to evaluate the selected diet by sheep in caatinga's pasture. On this pasture, the sheep are skilled to select the diet, changing during the phenological phases, trying to form a diet of better nutritive value. Forages as A. brasiliana, P. maximum cv. Massai and M. caesalpiniaefolia, can be considered an interesting food source to ewes kept in the caatinga.